Front Cover: Asymmetric Synthesis of Multi‐substituted Prolines via a Catalytic 1, 3‐Dipolar Cycloaddition Using a Monocationic ZnIIOAc Complex of a Chiral Bisamidine Ligand, Naph‐diPIM‐dioxo‐R (ChemCatChem 22/2020). Issue 22 (15th October 2020) - Chaithanya Kiran, I. N.; Fujita, Kazuki; Tanaka, Shinji; Kitamura, Masato
Abstract : The Front Cover shows a highly efficient catalytic enantioselective 1, 3‐dipolar cycloaddition of tridentate‐type α‐imino esters and acrylates. In their Communication, I. N. Chaithanya Kiran et al. explain the catalyst's design concept and its performance for the reaction. The catalyst is a monocationic zinc acetate complex of a chiral bisamidine‐type bidentate ligand. An anionic acetate ligand of the Lewis acidic Zn complex acts as a Brønsted base to facilitate a smooth intramolecular deprotonation to generate an imino N, O ‐ cis ‐Zn enolate. The oxygen atoms of two dioxolanes of the ligand form a C 2 chiral scaffold, in which the Zn enolate position is well controlled by a non‐bonding n‐π* interaction. The catalyst shows high activity, diastero‐/enantio‐/regio‐selectivity, productivity, and broad generality. This reaction provides a path for the synthesis of pyrrolidine‐containing chiral bioactive compounds, ligands and organocatalysts. More information can be found in the Communication by I. N. Chaithanya Kiran et al.